Educação estética, artes e imaginário: uma jornada arquetípica na transformação de sentidos existenciais - Gallina, Franciele Silvestre (2017)
The theme of this study, linked to the research line Educational Processes and Language, was about aesthetic education contemplated in the light of the imaginary. In order to do so, the problematic was: Can aesthetic educational processes developed through the imaginative function enable human beings to modify their reality redefining actions and existential senses? The main objective tried to respond to this questioning. The specific objectives were: to investigate whether the primacy of subjective experience creates effective phenomena of cultivating diferents forms of wisdom, knowledge and care; to observe whether educational processes coined by the sensible-intelligible path would contribute to the expansion of consciousness and creative convergence; to understand the meaning of the aesthetic educational workshop for the participants based on the Gilbert Durand (1993) theory. It is a qualitative, hermeneutic-phenomenological research. The working method was a workshop supported by the essential anthropology formulated by Leloup (1998) and by the basic dimensions of Aesthetic Education: Aisthesis, with creative activities such as dramatic improvisation, drawing, painting, among others, promoters of aesthetic experiences through the arts; Poiesis, with the construction of projects supported in the emergent significations of the previous stage, and Katharsis, with reflections and socialization of the experienced process. The research instruments consisted of an archetypal design and a narrative. Ten meetings were held with subjects of both sexes, ranging from 21 to 60 years old, joined in three distinct work groups: one from formal education, composed of educators from the public network; another one of permanent education, formed by professionals and trainees from various health areas and a third of non-formal education, made up of participants from different professions. All of them are residents and workers from the Northern Region of Rio Grande do Sul, Brazil. In order to understand the emerging information, Durand (1993) proposed a myth-critic approach, which aims to extract redundant themes from the meanings of director myths. From this configuration, the thesis proves that the aesthetic educational processes developed through the imaginative function allowed for the experiences that could modify the reality of the people, giving a new meaning to actions and their existential senses. The results of the research consisted of an Archetypal Journey set up by eight director myths, which unravelled the conflicts of those who entered the labyrinth of themselves and, in the face of dangers and difficulties, sought to find the centre of their being, just as he did the Hero Theseus. The myth of Creation emerged to signify the end of Chaos, a first elementary phase, permeated by an organizational energy, indicating that the exemplary myth helps the human, so that he can establish order, with the help of Cronus, and with Kairos as a companion, enjoy the opportune moment. In addition, by holding firmly on Ariadne's thread, sew the network of wisdom, knowledge and care woven here by the myths of Chiron and Athena, as an ideal of basic formation, so that the human being contemplates his evolutionary cycle marked by the myth of the Eternal Return.